Bonding, Bridging, and Linking Social Capital among Millennial Farmers in Rural Agribusiness - Artreurt Yoseph Merung; Stella Pingkan Paendong (Indonesian Journal of Business and Entrepreneurship Research, 2026)
Farmer regeneration has become a critical issue in rural agricultural development, particularly as young farmers are expected to sustain agribusiness transformation in an increasingly digital and market-oriented era. This study aims to identify the elements of social capital among millennial farmers in Keroit Village, South Minahasa Regency, and to explain how these elements shape rural agribusiness capacity. Using a qualitative-dominant design, data were collected from 24 millennial farmers through two focus group discussions, eight in-depth interviews, field observation, documentation, and a descriptive Likert-scale questionnaire. The questionnaire consisted of 25 items covering five dimensions of social capital: trust, social networks, social norms, social participation, and information access. Qualitative data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while Likert scores were used as descriptive support to triangulate the qualitative findings. The results show that trust received the highest score and was categorized as very strong, followed by social norms and social participation. In contrast, social networks and information access were categorized as moderate. These findings indicate that the social capital structure of millennial farmers in Keroit Village is dominated by bonding capital, while bridging and linking capital remain limited. The study contributes to social capital and farmer regeneration literature by showing that strong local solidarity does not automatically produce agribusiness competitiveness unless it is connected to broader markets, institutions, digital information, and innovation networks. Strengthening millennial farmers therefore requires transforming Mapalus-based cooperation into wider agribusiness capacity through partnerships, institutional assistance, digital information access, financing opportunities, and youth leadership development.